Pengaruh Motivasi Terhadap Minat Mahasiswa Untuk Menjadi Wirausaha Mahasiswa Program Studi Akuntansi Universiats Triatma Mulya - Dewi, Tiara Kusuma (Universitas Tabanan, 2023)
Being an entrepreneur is a decision about a profession that can be shaped. One of the places where someone can be educated or trained to become an entrepreneur is at a university, such as Triatma Mulya University. But unfortunately, because of fear of failure and lack of motivation, students often discourage their interest in becoming entrepreneurs and prefer to look for work rather than starting a business. Therefore, it is important to know the extent to which entrepreneurial motivation can attract students to entrepreneurship, especially in the Triatma Mulya University Management Study Program. The purpose of this study was to find out how the influence of motivation on the interest in entrepreneurship of students of the Triatma Mulya University accounting study program. Indicators of entrepreneurial motivation are ambition for freedom, self-realization, and pushing factors. This research is quantitative. Sampling was carried out by distributing questionnaires, using the sampling method to 64 respondents who were all students. The analysis technique used is multivariate analysis with SPSS version 20 and an alpha of 5%. The results of this study indicate that entrepreneurial motivation with an ambition for freedom indicator is the factor that has the greatest influence on students' entrepreneurial interest at Triatma Mulya University.